Berebut Wacana: Hilangnya Etika Komunikasi di Ruang Publik Dunia Maya - Mustofa, Saiful (Jurnal Studi Agama dan Masyarakat, 2019)
The background of this study concern to phenomenon a communication ethics no longer exist in the social media public sphere. Social media, as one of the products of the digital revolution being a free stage to spread anxiety; ethnic, racial, and religious sentiments (SARA) to the legitimacy of the authority of truth. By using critical hermeneutic approach of J